Diagnostic efficacy of neutrophil to lymphocyte ratio (NLR) in oral potentially malignant disorders and oral cancer - Shruti Singh; Jaya Singh; Roop Ganguly; Shaleen Chandra; Fahad M Samadi; Shaista Suhail (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Inflammation is considered to be the seventh hallmark of cancer and plays a pivotal role in all stages of tumor development. Systemic inflammatory responses in particular neutrophil to lymphocyte ratio (NLR) have garnered immense attention of current researchers and its role is well proven in various solid malignancies. Its prognostic role in oral cancer have been extensively studied. However, its diagnostic role is yet to be explored. The current study aims to investigate diagnostic utility of NLR in oral potentially malignant disorders and oral cancer, when compared to normal subjects. Methods: A total of 150 subjects were involved in the study, a total of 2.5 ml of blood was drawn from the median cubital vein of the patient in an EDTA vial and hematological parameters were assessed using Erba-Transasia B7256 Autoanalyzer and reassessed manually by two experts. Statistical Analysis: The NLR values were recorded and tabulated as Mean ± S.D. and comparisons were analyzed using Kruskal Wallis and Mann Whitney post hoc U test. ROC curve analysis was performed to estimate cut-off values. Results: The NLR values when compared between the 3 groups were statistically significant (P < 0.001). The cut off value between disease and normal subject was 2.33, while the cut-off value between potentially malignant and malignant condition is 3.20. Conclusion: NLR can be a valuable diagnostic adjunct in oral cancer and potentially malignant disorders of oral cavity.